Documentation, Computer, and Classification - Ranganathan, S. R. (Journal of Information and Knowledge, 2002)
A computer can be of use in repetitive work in a library, wherever it is viable. But it cannot be used for classification for which judgement is necessary. The memory of a computer should be fed with classified main entries to enable it to produce for browsing a set of entries in classified sequence. The Freely-Faceted Classification is the most evolved scheme designed so far, for use in computer. Version 3 of CC is an example. Continuing concerted research is necessary in the fields of design of depth classification and of building of computer.